Using lactate threshold to predict 5-km treadmill running performance in veteran athletes - Forsyth, Jacky; Burt, Dean; Ridley, Fiona; Mann, Christopher (Biology of Sport, 2017)
Measuring lactate threshold to predict endurance performance is difficult among veteran athletes, due to age-related decreases in net lactate concentration. The objective of this study was to determine whether lactate threshold, as assessed using the maximal deviation method (Dmax), which is not dependent on net values of lactate, could be used as a more valid measure of 5-km treadmill running performance than other methods of determining lactate threshold. Veteran runners (18 male and 18 female, aged 47.3±6.7 years) performed an incremental exercise test to establish mean treadmill velocity at lactate threshold using Dmax, a log-log method, a visual method, and a 4-mmol.L-1 method, and, on a separate occasion, completed a 5-km time trial. Mean treadmill velocity at Dmax was 12.2±1.8 km.h-1, not being significantly different to mean treadmill velocity (12.1±1.8 km.h-1) attained during the 5-km time trial (p>0.05); velocities were also significantly correlated (r=0.92, p<0.001), and limits of agreement narrow (-1.61 to 1.35 km.h-1). Correlations were weaker and limits of agreement wider for the other methods of lactate threshold determination. Using a two-way, mixed-methods ANOVA, there was no significant effect of sex when using the different methods of determining Tlac (F4,136=3.70, p=0.15). Mean treadmill velocity, when using Dmax for determining lactate threshold, can be used to predict 5-km running performance among male and female veteran athletes.